Identification and synthesis of metabolites of the new antiglaucoma drug - Alexander L. Khokhlov; Ilya I. Yaichkov; Anton А. Shetnev; Sergey A. Ivanovsky; Mikhail K. Korsakov; Mikhail A. Alexeev; Olga A. Gasilina; Nikita N. Volkhin; Sergey S. Petukhov (Belgorod National Research University, 2024)
Introduction: The determination of biotransformation products is an essential part of the preclinical trial of original medicines. These studies have not been conducted before for the new drug 5-[5-(trifluoromethyl)-1,2-oxazole-3-yl]-furan-2-sulfonamide. Identification and synthesis of metabolite substances are necessary for subsequent tests of bioavailability, linearity of pharmacokinetics, accumulation, distribution and excretion. Materials and methods: The study was carried out on Wistar rats and rabbits of the Soviet Chinchilla breed. The substance of the drug was administered to animals intraperitoneally. The collection of animal blood samples was performed before administration and 1 h, 2 h, 4 h, 24 h after administration into K3EDTA-tubes. A part of each sample was centrifuged to separate the plasma. Rat urine samples were taken before administration and at intervals of 0-2 h, 2-4 h, 4-6 h, 6-24 h after administration of the drug. The HPLC-MS/MS method was used to identify metabolites in biological fluids. The assumed biotransformation products were synthesized after preliminary analysis. The structure of the obtained substances was confirmed by NMR spectroscopy and high-resolution mass spectrometry. Then, a comparison was carried out with the compounds identified in biological fluids by retention time, ratios of chromatographic peak areas at the main MRM-transitions using HPLC-MS/MS. Results and discussion: A metabolite formed by addition an oxygen atom to a drug molecule, as well as an acylated metabolite were detected during the analysis of plasma and blood samples. A compound with an increased molecular weight of 1 dalton compared to the drug substance was also present in a rat urine. N-hydroxy-5-[5-(trifluoromethyl)-1,2-oxazole-3-yl]-furan-2-sulfonamide, 5-[5-(trifluoromethyl)-1,2-oxazole-3-yl]-furan-2-sulfonic acid, which could potentially be obtained during biotransformation, as well as N-acetyl-5-[5-(trifluoromethyl)-1,2-oxazole-3-yl]-furan-2-sulfonamide were synthesized. Repeated HPLC-MS/MS tests confirmed the correctness of the initial hypothesis. It was found that a sulfonic acid derivative is formed in urine as a result of decomposition of N-hydroxymetabolite during sample collection. Conclusion: The studied drug is metabolized by formation of two metabolites: N-hydroxy-5-[5-(trifluoromethyl)-1,2-oxazole-3-yl]-furan-2-sulfonamide and N-acetyl-5-[5-(trifluoromethyl)-1,2-oxazole-3-yl]-furan-2-sulfonamide. N-hydroxymetabolite is able to decompose in biological fluids samples with formation of 5-[5-(trifluoromethyl)-1,2-oxazole-3-yl]-furan-2-sulfonic acid.